Implementación de una aplicación web para la gestión de bolsa de empleo utilizando la tecnología Lambda y Linq con .NET7 - Guerrero Dutan, Edisson Alexander (2024)
The main objective of this research study was the implementation of a web application of an employment exchange at the National University of Chimborazo seeks to facilitate the insertion of students into the labor market, allowing them to apply their knowledge to real problems. The job exchange centralizes job offers, speeding up the search with LINQ and lambda expressions. The objective of this research project is the implementation of a web application through lambda and LINQ technologies so that students can apply for different job offers and their evaluation through the usability of the web application. The development of the web application was based on Razor technologies on the Front-End side, thus giving us greater compatibility with the dependencies and components of the .net7 development framework, on the other hand, it will fulfill the function of the Back-End based on the MVC (Model View Controller) architecture pattern that allows the separation and organization of the code, additionally it uses the C# language and the domain-oriented architecture. In this research, the quantitative method was used, taking as a principle the usability evaluation criteria of the ISO 9241 standard. The quantitative and statistical analysis method was used to examine the data collected. Observation, interview, and survey techniques were used. The evaluation of usability according to ISO 9241 of the web application reveals a high level of efficiency, as it is evident that none of the technicians had more than 2 errors in the 9 activities, the level of satisfaction is within the range of 88.88% and 100% and in the usability tests the majority of users expressed ratings of excellent and very good confirming the positive user experience and ease of interaction with the application to perform specific activities. The combination of LINQ and Lambda Expressions offers an improved user experience, increased performance, and a significant reduction in lines of code. In a web application, this technology simplifies information management, allowing students to apply and companies to manage applications efficiently.